A clinical retrospective study comparing thoracic epidural catheterization between awake and anesthetized patients - Lee, Seok-Jin; Cho, Sung-Ae; In, Chi Bum; Sung, Tae-Yun; Kang, Po-Soon (Anesthesia and pain medicine (Korean society of anesthesiologists), 2019)
Background: The clinical outcomes and safety of thoracic epidural catheterization in anesthetized adult patients has not yet been established. The purpose of this study was to compare clinical differences between epidural catheterization performed before and after anesthesia for postoperative pain control. Methods: The medical records of 549 patients who received thoracic epidural catheterization before (awake group, n = 303) or after (anesthetized group, n = 246) induction of anesthesia for major abdominal surgery were reviewed retrospectively. Results: The catheter insertion time (1.6 ± 1.5 vs. 1.1 ± 1.2 min; 95% confidence interval [95% CI], 0.3–0.8; effect size, 0.368; P < 0.001) and number of attempts required for successful epidural catheterization (1 [1, 3] vs. 1 [1, 2], P = 0.003) were increased in the awake group. The incidence rates of dural puncture, vascular injury and postoperative paresthesia were similar between the two groups. The median surgical site numerical rating scale pain score (0 = no pain, 10 = worst pain imaginable) was lower in the awake group than in the anesthetized group (3 vs. 4 on postoperative day 1, P < 0.001; and 2 vs. 3 on postoperative day 3, P = 0.002). Serious complications, including meningitis, epidural abscess, epidural hematoma, spinal cord injury, and paraplegia, were not observed in either group. Conclusions: Successful epidural catheterization before induction of anesthesia required more attempts versus after anesthesia. Overall complication rates of thoracic epidural catheterization were similar regardless of the timing of the procedure. KCI Citation Count: 0